Muscle radiodensity and mortality in patients with colorectal cancer - Kroenke, Candyce H. (Cancer, 2018)
BACKGROUND: Low skeletal muscle radiodensity (SMD) is related to higher mortality in several cancers but the association with colorectal cancer (CRC) prognosis is unclear. METHODS: This observational study included 3,262 men and women from the Kaiser Permanente Northern California population diagnosed from 2006–2011 with stages I–III CRC. We evaluated hazard ratios for all-cause and CRC-specific mortality of low SMD, assessed by computed tomography using optimal stratification, relative to patients with normal SMD. We also evaluated the cross-classification of categories of low vs. normal SMD and muscle mass (MM), with outcomes. RESULTS: Median follow-up was 6.9 years. Optimal stratification cutpoints for SMD were 32.5 in women and 35.5 in men. In multivariate-adjusted analyses, compared to those with normal SMD levels, CRC patients with low SMD showed higher overall (hazard ratio [HR]=1.61, 95% confidence interval [CI]:1.36–1.90) and CRC-specific (HR=1.74, 95% CI:1.38–2.21) mortality. Patients with low SMD and low MM (i.e., sarcopenia) had the highest overall (HR=2.02, 95% CI: 1.65–2.47) and CRC-specific (HR=2.54, 95% CI: 1.91–3.37) mortality rates. CONCLUSION: In patients with CRC, those with low SMD had elevated risks of disease-specific and overall mortality, independent of MM or adiposity. Clinical practice should incorporate body composition measures into the evaluation of CRC patient health status.